2010
DOI: 10.1007/s12272-010-1019-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of daidzin and its aglycon, daidzein, on the scopolamineinduced memory impairment in male mice

Abstract: In this study, the effect of daidzin or daidzein isolated from Pueraria lobata on the memory impairments induced by scopolamine was assessed in male mice using the passive avoidance and the Morris water maze tasks. Administration of daidzin (5 mg/kg) or daidzein (5 mg/kg) significantly reversed the scopolamine (1 mg/kg)-induced cognitive impairments in male mice as evidenced by the passive avoidance test (p < 0.05) and on the Morris water maze test (p < 0.05). Moreover, the ameliorating effects of daidzin or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Moreover, intraperitoneal administration of puerarin in rats at the onset of middle cerebral artery occlusion (MCAO) considerably improved neurological functions, and diminished infarct and oedema volume . Daidzin and daidzein have also been shown to improve brain functions (Kouki et al, 2003;Nakagawa et al, 2006;Kim et al, 2010;Zhang et al, 2010). These findings confirm the in vivo efficacies of the three isoflavonoids on the central nervous system.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Moreover, intraperitoneal administration of puerarin in rats at the onset of middle cerebral artery occlusion (MCAO) considerably improved neurological functions, and diminished infarct and oedema volume . Daidzin and daidzein have also been shown to improve brain functions (Kouki et al, 2003;Nakagawa et al, 2006;Kim et al, 2010;Zhang et al, 2010). These findings confirm the in vivo efficacies of the three isoflavonoids on the central nervous system.…”
Section: Discussionmentioning
confidence: 71%
“…Daidzein and daidzin can be found in soy bean as well as Gegen (Verkasalo et al, 2001;Kim et al, 2010). Daidzein is an aglycone of puerarin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that vasicine, deoxyvasicine and their analogs alkaloids are strong cholinesterases inhibitors in vitro Zhao et al, 2013;Zheng et al, 2009Zheng et al, , 2011, and they have the potential improvement learning and memory effects in vivo. In addition, some flavonoids, such as luteolin, oroxylin A and daidzin among others, have been proven with potential anti-amnesic effect (Yoo et al, 2013;Kim et al, 2007Kim et al, , 2010. Therefore, these exciting results prompted us to perform a series of experiments to evaluate the improvement learning and memory effects of the total extract and two mainly fractions of total alkaloids and total flavonoids from APP.…”
Section: Introductionmentioning
confidence: 99%
“…16) Health effects of daidzin have been proved on memory impairment, hepatic failure, and glucose homeostasis. [17][18][19] It was also reported that glycitin has preventive effect on bone loss and osteonecrosis. 20,21) However, to our knowledge, there are few studies that have been done on the effects of glycoside-form isoflavone supplementation on lipid metabolism associated with diabetes mellitus.…”
mentioning
confidence: 95%